Pengaruh Kualitas Pelayanan dan Kepuasan Pasien Non JKN Terhadap Kinerja Rumah Sakit Melalui Loyalitas Pasien - Daniel Novian Dharma Setia Budi; Rokiah Kusumapradja (Jurnal Health Sains, 2022)
Hospitals as a complex organization have experienced challenges in the era of the Universal Health Coverage since 2014. Quality of service, patient satisfaction and patient loyalty are factors that support hospital performance. The study was  to see the impact of non UHC health service and patient satisfaction on hospital performance through the level of patient loyalty. The study was at Imanuel Way Halim Hospital Bandar Lampung in September and October 2019 with 178 respondents consisting of non UHC patients. This study uses the Structural Equation Model (SEM) to analyze the pattern of variable relationships. The independent variable is service quality and patient satisfaction, intervening variable is patient loyalty, and the dependent variable is hospital performance. The results showed that customer of Imanuel Way Halim Hospital had good fanatism. The hospital financial performance was good, and respondents rated the quality of hospital services as good, so that they were satisfied and loyal to the hospital. Patient loyalty is determined not only by the quality of service. These three factors (service quality, patient satisfaction and patient loyalty) influence the performance of the hospital.